The toxicity of extracts from the bark and leaves of Zizyphus talanai (Blanco) Merrill of Family Rhamnaceae against brine shrimp (Artemia salina L.). - Estaniel, Ana Mae (1999.)
The toxicity of the bark and of Zizyphus talanai (Blanco) Merrill from the family Rhamnaceae against brine shrimp (Artemia salina L.) were tested using the three solvents namely; methanol, ethanol (95), and dichloromethane., Screening of the bark showed the presence of alkaloids, saponins and tannins. The bark and have lowest LC50 in the dichloromethane crude extract. The LC50 of the bark, which was determined by arithmetic method was 72 ug/ml and 56 ug/ml for the sample. Four fractions were obtained from the column chromatography of the dichloromethane extract of. Result of toxicity test against brine shrimp showed that only the fourth fraction had the lowest LC50 at 940 ug/ml. Thin layer chromatography showed that the four fractions contain saponins, tannins, phenols, and anthraquinones and / or coumarines.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Ziziphus talanai -- Barks; Ziziphus talanai -- Leaves